Comparison of fresh and preserved decellularized human corneal lenticules in femtosecond laser-assisted intrastromal lamellar keratoplasty. (15th September 2022) - Yu, Na; Chen, Shuilian; Yang, Xifeng; Hou, Xiangtao; Wan, Linxi; Huang, Yuke; Qiu, Jin; Li, Yan; Zheng, Hua; Wei, Han; Zeng, Chenguang; Lei, Lei; et al.
Abstract: Substantial evidence has demonstrated the application of fresh and decellularized human corneal lenticules from increasing myopic surgeries. Further preservation of decellularized corneal lenticules would extend its clinical application. However, whether fresh and preserved decellularized lenticules have the same effects in vivo, including refractive correction, remains unclear. Here, we made comprehensive comparisons between fresh human lenticules (FHLs) and preserved decellularized human lenticules (DHLs). Another group of decellularized lenticules was combined with crosslinking for potential keratoconus therapy. Optical transparency, biomechanical properties, and fibrillar ultrastructure were analyzed to evaluate the DHLs and crosslinked DHLs (cDHLs) in vitro . The DHLs retained high transparency and regular ultrastructure, with genetic materials mostly being eliminated. The strength of lenticules in the cDHL group was markedly increased by crosslinking. Moreover, after storage in glycerol for 3 months, the lenticules were reimplanted into rabbit corneal lamellar pockets assisted by a femtosecond laser. The rabbits were followed for another 3 months. There were no obvious rejective complications in any of the three groups. From 1 week to 3 months postoperatively, the host corneas of the FHL group remained highly transparent, while slight hazes were observed in the DHL group. However, the corneas of the cDHL group displayed opacity throughout the 3-month postoperative period. Furthermore, all the lenticules could effectively induce corneal steepening and refractive changes. Taken together, our data indicated that FHLs are ideal inlay products, whereas preserved DHLs could be an alternative for intrastromal lamellar keratoplasty. Our study provides new insights into the clinical application of human lenticule recycling. Statement of significance: Currently, substantial evidence has demonstrated the application of fresh and decellularized human corneal lenticules from increasing myopic surgeries. Further preservation of decellularized lenticules would extend its clinical application. However, whether fresh and preserved decellularized lenticules have the same effects in vivo, including refractive correction, remains unclear. Herein, we decellularized human lenticules with or without mechanically strengthened crosslinking. After storage in glycerol for 3 months, the lenticules were reimplanted into rabbit corneas. Comprehensive comparisons were performed among fresh human lenticules (FHLs), decellularized human lenticules (DHLs) and crosslinked DHLs. Our study indicated that FHLs are ideal inlay products, whereas preserved DHLs could be an alternative for intrastromal lamellar keratoplasty. Our study provides new insights into the clinical application of human lenticule recycling. Graphical abstract: Image, graphical abstract